The Chages in Sex Hormones in Female Working in Battries Manufacturing Plant - A. Taher, Mohammed; A.Hammadi, Salim; A.Ali, Ali (Iraqi Journal of Pharmaceutical Sciences, 2017)
Lead has toxic effects on reproduction of both male and female. It can cause decreased sex drive , infertility and abnormal menstrual cycle in women. This study was designed to evaluate the effect of exposure to lead in batteries female workers on sex hormones level in the serum.Thirty nine (39) female workers (volunteers) in Iraqi Batteries Manufacturing Plants, Al-Waziriya / Baghdad were participated in this study. They are classified into 3 groups, first group included fourteen (14) female that have been employed for 1-7 years , second group included thirteen (13) female that have been employed for 8-14 years , third group included twelve (12) female have been employed for15-22 years and and fourteen females were included as the control . Blood lead level, serum FSH, LH, prolactin and total testosterone were measured and compared for all subjects.The results indicated that mean of blood lead levels (BLL), testosterone levels were highly significant in all worker groups compared to the control (p<0.005).Prolactin levels in group I and FSH in group III were significantly higher than that in control ( P< 0.005) and (P<0.05) respectively. LH levels in groups II and III were significantly higher than that in control (P<0.05, P<0.005 respectively). High incidence of hirsutism (48%) and miscarriages (50%) were observed in worker groups compared to control (11%). The results indicated that there are hormonal changes in female workers exposed to lead associated with increased incidence of hirsutism and miscarriages compared to non exposed females .Key words: Lead , Sex hormones hyperandrogenemia